1984
DOI: 10.1111/j.1365-2125.1984.tb02353.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of digoxin alone and in the presence of indomethacin therapy.

Abstract: The effects of maintenance indomethacin therapy on single dose digoxin pharmacokinetics and dynamics were studied in six healthy volunteers with normal renal function. Indomethacin did not alter the elimination half‐life, systemic clearance or distribution of digoxin. No pharmacodynamic interaction as assessed by changes in the systolic time intervals QA2 and LVET was found. This study does not lend support for a significant digoxin‐indomethacin interaction in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
2
Order By: Relevance
“…Some studies in healthy volunteers have failed to demonstrate a significant interaction between digoxin and aspirin (Fenster et al 1982a) or between digoxin and indomethacin (Finch et al 1984), but other studies report a 30% rise in serum digoxin concentration attributable to aspirin (lsbary et al 1982) and a 25 to 55% increase in serum digoxin concentration following the addition of indomethacin (Isbary et al 1982;Koren 1985). It has been suggested that the potential for interaction between indomethacin and digoxin may be greater in patients with reduced renal function (Marcus 1985).…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 95%
“…Some studies in healthy volunteers have failed to demonstrate a significant interaction between digoxin and aspirin (Fenster et al 1982a) or between digoxin and indomethacin (Finch et al 1984), but other studies report a 30% rise in serum digoxin concentration attributable to aspirin (lsbary et al 1982) and a 25 to 55% increase in serum digoxin concentration following the addition of indomethacin (Isbary et al 1982;Koren 1985). It has been suggested that the potential for interaction between indomethacin and digoxin may be greater in patients with reduced renal function (Marcus 1985).…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 95%
“…Many of the studies that failed to demonstrate an interaction between NSAIDs and digoxin were performed in healthy volunteers whose renal function did not deteriorate during NSAID therapy (Fenster et al 1982;Finch et at. 1984;Verbeeck 1990).…”
Section: Digoxinmentioning
confidence: 97%
“…La preparación diluida debe ser administrada inmediatamente y el remanente debe ser descartado. La indometacina puede prolongar la vida media de digoxina, amikacina y gentamici-na [114][115][116][117][118][119][120][121][122] y es incompatible con aminoácidos, gluconato cálcico, dobutamina, dopamina y gentamicina. Es compatible con furosemida, insulina, cloruro potásico y bicarbonato de sodio 123 .…”
Section: Indometacinaunclassified
“…Los hallazgos son controvertidos, sin embargo, no lo son en cuanto al efecto diferencial de la administración en bolo frente a la infusión lenta 107,113,144,230 . Parece que el efecto de la indometacina sobre la reducción de la perfusión cerebral podría ser más precoz en el bolo que en la infusión lenta 114 , si bien no existen diferencias en el efecto global o en la duración de éste si el período de observación es más prolongado 114,147 , pero el período de observación fue corto en dos estudios (30 y 60 min) 108, 224 . Administrando cada dosis durante más de 30-60 min parecen limitarse algunos de los efectos negativos sobre el flujo sanguíneo.…”
Section: ¿Efectos Diferentes De Indometacina E Ibuprofeno En El Cerebunclassified